Influence of microclimate conditions on the cumulative exposure of nursery pigs to swine influenza A viruses. Issue 1 (22nd September 2017) - Ferreira, J. B.; Grgić, H.; Friendship, R.; Nagy, É.; Poljak, Z.
Summary: The objective of this study was to investigate the association between environmental temperature and humidity and the presence of antibodies for two specific strains of swine influenza viruses: A/SW/ON/105‐56/12/H3N2 (H3N2_D) and A/SW/ON/84/2012/H1N1 (H1N1_P). A cross‐sectional study was performed in a commercial farm, and a total of 450 pigs at 10 weeks of age were blood sampled, by sampling 10 pigs per week for 45 weeks corresponding to 45 batches. Exposure of pigs to H3N2_D and H1N1_P virus was assessed by haemagglutination inhibition assay (HI), and a result of ≥1:40 was considered as indication of a positive exposure status for a specific strain. The selection of those two viruses was based on the fact that H1N1 was the dominant virus in Ontario herds, and H3N2 had been previously isolated in this particular farm. Environmental conditions were recorded through a portable device every 5 min and then summarized using descriptive statistics. The association between HI titres and environmental microconditions, in the nursery, was evaluated through random effect linear and logistic regression. The results showed that the prevalence for H1N1_P was high throughout the study (≥70%); however, for H3N2_D, the seroprevalence declined by the end of the study period. Results also showed an association between cumulative exposure to the viruses and temperature and relative humidity ( p < .05). These results suggest that microclimate conditions can influence transmission patterns of influenza viruses in swine barns, and that even a herd with relatively simple demographics could have persistent and cocirculation of two different influenza A viruses IAV strains.